Sleep quality and burnout in higher education teachers - Italo Everton Bezerra Barbosa; Isabela Saura Sartoreto Mallagoli; Meiry Fernanda Pinto Okuno; Cassiane Dezoti da Fonseca; Angélica Gonçalves Silva Belasco (Rev Rene)
Objective: to evaluate the association of sleep quality and the presence of burnout syndrome with the epidemiological profile of higher education teachers. Methods: an observational, analytical, cross-sectional study of 140 teachers, using the Pittsburgh Sleep Quality Index and the Maslach Burnout Inventory. Results: in the sample, the majority was female (54.3%), aged between 26 and 40 years (58.6%). There was a predominance of teachers with a specialist title (48.6%), with a salary range of up to R$ 5,000.00 (85.7%), with two or more employment relationships (52.1%). It was found that teachers who received more than R$ 5,000.00 (p=0.003), with two or more jobs, classified the usual sleep efficiency as poor/feeble (p=0.027). However, those with good subjective sleep quality had lower scores in the Emotional exhaustion (p=0.005) and Depersonalization domains in relation to the syndrome (p=0.023). Conclusion: several factors contribute to the development of sleep-related disorders in teachers, making them more susceptible to the manifestation of burnout. Contributions to practice: the results can support preventive measures for the health of teachers and maintain the quality of their work activities, aiming to reduce the mediation effect of the variables that favor psychological exhaustion.